Improving neurophysiological biomarkers for functional myoclonic movements. (June 2018) - Beudel, M.; Zutt, R.; Meppelink, A.M.; Little, S.; Elting, J.W.; Stelten, B.M.L.; Edwards, M.; Tijssen, M.A.J.
Abstract: Introduction: Differentiating between functional jerks (FJ) and organic myoclonus can be challenging. At present, the only advanced diagnostic biomarker to support FJ is the Bereitschaftspotential (BP). However, its sensitivity is limited and its evaluation subjective. Recently, event related desynchronisation in the broad beta range (13–45 Hz) prior to functional generalised axial (propriospinal) myoclonus was reported as a possible complementary diagnostic marker for FJ. Here we study the value of ERD together with a quantified BP in clinical practice. Methods: Twenty-nine patients with FJ and 16 patients with cortical myoclonus (CM) were included. Jerk-locked back-averaging for determination of the 'classical' and quantified BP, and time-frequency decomposition for the event related desynchronisation (ERD) were performed. Diagnostic gain, sensitivity and specificity were obtained for individual and combined techniques. Results: We detected a classical BP in 14/29, a quantitative BP in 15/29 and an ERD in 18/29 patients. At group level we demonstrate that ERD in the broad beta band preceding a jerk has significantly higher amplitude in FJ compared to CM (respectively −0.14 ± 0.13 and +0.04 ± 0.09 ( p < 0.001)). Adding ERD to the classical BP achieved an additional diagnostic gain of 53%. Furthermore, when combining ERD with quantified and classical BP, an additional diagnostic gain of 71% was achieved without loss of specificity. Conclusion: Based on the current findings we propose to the use of combined beta ERD assessment and quantitative BP analyses in patients with a clinical suspicion for all types of FJ with a negative classical BP. Highlights: Differentiating between functional jerks and organic myoclonus is often difficult. The sensitivity of a positive bereitschaftspotential for diagnosing FJ is low. FJ are preceded by event related desynchronisation (ERD) in the beta band. Combining beta ERD and BP improves diagnosing FJ. The ERD method is of special relevance in possible FJ patients with a negative BP.